'From blood to blood': de‐differentiation of hematopoietic progenitors to stem cells. (6th June 2014) - Pereira, Carlos‐Filipe; Lemischka, Ihor R; Moore, Kateri
<x xml:space="preserve">Abstract</x> Recent studies have reported that fibroblasts or differentiated pluripotent cells can be reprogrammed with transcription factors (TFs) into cells with hematopoietic potential. A study published in Cell now suggests that committed blood precursors may provide a source for blood stem cell transplantation after reprogramming (Riddell et al, 2014). The authors report that a combination of eight TFs reprogram murine committed blood progenitors into long‐term engrafting and serially transplantable hematopoietic stem cells with a molecular signature similar to their endogenous counterparts.